A computer model for assessing agro-climatic and edaphic feasibility for rubber cultivation in the traditional tract - Vilasachandran K; Motial V S; Sharma M R; Usha K (Indian Journal of Natural Rubber Research, 1992)
A computer model has been designed to access the agro-climatic and edaphic feasibility of an area in traditional tract for commercial rubber cultivation. This model devised in Lotus 1-2-3 employing 'nested @ IF function' is useful to indicate the suitability of an area against each agro-climatic and edaphic factor based on pre-defined suitability indices and to infer the overall agro-climatic and edaphic suitability of an area for commercial rubber cultivation. The model can accomodate changes in suitability indices and is user-friendly.
Keywords: Hevea; Hevea; Lotus 1-2-3; Lotus 1-2-3; Nested; Nested